Realizacja zajęć wynikających z artykułu 42 Karty Nauczyciela w aspekcie zróżnicowania form aktywności fizycznej - Ostrowska, Małgorzata (Pedagogiczny wymiar kultury fizycznej i zdrowotnej w życiu współczesnego człowieka, 2016)
Since September 1st 2009, all teachers have been required to carry out activities under Article 42 of the Teachers’ Charter, within working hours. The aim of these activities is to increase educational opportunities for students by working with gifted students or those with learning difficulties, and developing individual interests. Therefore, in the field of school physical education, an additional opportunity has been created for the realisation of a variety of physical activities, including sport, recreation, tourism and health. Referring to the arrangements for the implementation of the working hours, which is mentioned in Article 42, point 2 of the Teacher’s Charter, studies have been conducted on a group of 78 physical education teachers in primary, lower secondary and upper secondary schools. The research, carried out by a diagnostic survey at the methodical conference in 2014, aimed at gathering opinions on: forms and areas of the implementation of the activities, assessment of the effectiveness of ongoing didactic and educational forms of activities, and determining whether the activities organised by teachers take into account the needs and interests of students, and fundamental canons of methodology of physical education. Gathered results confirm the thesis of the superiority of sport activities over the recreational ones and low status of health education in the implementation of corrective and compensatory gymnastics.